A well-known but previously misidentified odontoglossum (orchidaceae: oncidiinae) from Ecuador - Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2013)
A previously misidentified species of Odontoglossum (Orchidaceae, Oncidiinae), from the botanically well explored western slopes of mount Pichincha in Ecuador is described and illustrated, and compared with similar species. The new species is most similar to O. cristatum, but differs in a larger plant habit with larger flowers that present a longer and straighter column with bifurcate wings, versus a more slender and more curved column with triangular, falcate column wings of O. cristatum.